(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Stress has been a common factor affecting all aspects of life includinginterpersonal relationships, work, school, and family. Coping strategies play acritical role in an individual’s physical and psychological well-being whenfaced with challenges and negative events. Also, coping can be viewed as anapproach driven to manage goals and utilize social resources such as co-workerand family support to achieve one’s goals. This paper focuses coping mechanismand occupational stress specific to gender.